(untitled) (Research, Society and Development, 2021)
The strength of the Brazilian economy comes from the success of micro and small companies, which is of fundamental importance for the achievement of the country’s economic development. Thus, the objective of this article is to analyze the behavior of 13 variables collected on level of companies from three tourist segments of the “paradise” called Jericoacoara in the State of Ceará through the application of discriminant analysis. The methodological option chosen in this study was the multivariate analysis of the relationships between the variables and the focus variable. For this purpose, discriminant analysis was adopted, which allows the identification of factors that have greater predictive capacity in relation to the phenomenon under study. The study showed that micro entrepreneurs have a medium level of use of their business management technologies. It is also verified that the Expense Notes, Accounting Organization and Access to Information variables are the ones with the greatest power of discrimination, that is, they are the variables that best discriminate the groups.